The COVID-19 Pandemic Impact on Breast Cancer Diagnosis: A Retrospective Study - Negrao, Erika Marina Solla; Cabello, Cesar; Conz, Livia; Mauad, Edmundo Carvalho; Zeferino, Luiz Carlos; Vale, Diama Bhadra (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective This study aimed to evaluate the diagnostic profile of breast cancer cases during the coronavirus disease 2019 (COVID-19) pandemic compared with the previous year.Methods It is a retrospective study of cases diagnosed by a reference service in the public health system of Campinas, SP, Brazil. Two periods were analyzed: March to October 2019 (preCOVID period) and March to October 2020 (COVID-period). All women diagnosed during the periods were included. The Chi-Squared or Fisher exact and Mann-Whitney tests were used.Results In the preCOVID and COVID periods, breast cancers were diagnosed, respectively, in 115 vs 59 women, and the mean ages at diagnosis were 55 and 57 years (p = 0.339). In the COVID period, the family history of breast cancer was more observed (9.6% vs 29.8%, p < 0.001), cases were more frequently symptomatic (50.4% vs 79.7%, p < 0.001) and had more frequently palpable masses (56.5% vs 79.7%, p = 0.003). In symptomatic women, the mean number of days from symptom to mammography were 233.6 (458.3) in 2019 and 152.1 (151.5) in 2020 (p = 0.871). Among invasive tumors, the proportion of breast cancers in stages I and II was slightly higher in the COVID period, although not significantly (76.7% vs 82.4%, p = 0.428). Also in the COVID period, the frequency of luminal A-like tumors was lower (29.2% vs 11.8%, p = 0.018), of triple-negative tumors was twice as high (10.1% vs 21.6%, p = 0.062), and of estrogen receptor-positive tumors was lower (82.2% vs 66.0%, p = 0.030).Conclusion During the COVID-19 pandemic, breast cancer diagnoses were reduced. Cases detected were suggestive of a worse prognosis: symptomatic women with palpable masses and more aggressive subtypes. Indolent tumors were those more sensitive to the interruption in screening.
Keywords: breast neoplasms; early detection of cancer; quality of health care; COVID-19; mammography